Biodesulfurization of Consortia Immobilized on Oil Palm Frond Biochar in Biotrickling Filters under Anoxic Conditions - Pajongsuk Sutarut; Benjamas Cheirsilp; Piyarat Boonsawang (Fermentation, 2023)
Biodesulfurization using biotrickling filters (BTFs) under anoxic conditions is a cost-effective method for biogas clean-up. To improve the performance of BTFs, the microbial consortia from the anaerobic pond of a swine farm (SW), the denitrification pond of a tuna factory (DN), and the UASB of the concentrated latex industry (LW) were immobilized on BTFs. In this study, the efficiency of BTFs immobilized with the microbial consortia for the reduction of H2S gas combined with the reduction of nitrate contained in wastewater was investigated. The results showed that H2S was completely removed at the inlet H2S concentration of 207.8–1476 ppmv with wastewater circulation under anoxic conditions. However, only the DN-BTF achieved H2S removal of 95.2% at an inlet concentration of 2500 ppmv. An increase in the N/S ratio (0.356–2.07 mol/mol) improved the H2S removal of the SW-BTF, LW-BTF, and DN-BTF but not the BTF-C. Moreover, the DN-BTF had the highest nitrate removal rate (71.1%) with an N/S ratio of 2.07 mol/mol. When oxygen was supplied in wastewater at DO = 3.60 ± 0.41 mg/L, sulfate was generated at a higher rate, but nitrite production was lower than at DO~0. After microbial community analysis, Proteobacteria were the main phyla involved in the biodesulfurization process.